2009
DOI: 10.1111/j.1439-0329.2008.00579.x
|View full text |Cite
|
Sign up to set email alerts
|

Physiological responses of cork oak and holm oak to infection by fungal pathogens involved in oak decline

Abstract: The aim of this research was to study the changes in net photosynthesis and stomatal conductance values in 3-year-old cork oak and holm oak seedlings growing in natural conditions and inoculated with Apiognomonia quercina, Biscogniauxia mediterranea, Botryosphaeria corticola and Pleurophoma cava. Throughout the 4-month experimental period, the evolution of visual external symptoms and the values of physiological variables were periodically recorded. All pathogens caused stem lesions around the infection point;… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
43
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(43 citation statements)
references
References 17 publications
0
43
0
Order By: Relevance
“…Earlier, P. cava has been reported as an endophytic species involved in the aetiology of decline of Mediterranean Quercus trees [72], [73]. The fungus M. nivalis is a snow mold with a temperature minimum of −5°C for growth [74].…”
Section: Discussionmentioning
confidence: 99%
“…Earlier, P. cava has been reported as an endophytic species involved in the aetiology of decline of Mediterranean Quercus trees [72], [73]. The fungus M. nivalis is a snow mold with a temperature minimum of −5°C for growth [74].…”
Section: Discussionmentioning
confidence: 99%
“…appear to be weak pathogens involved in oak decline; but those oaks infected may be less likely to survive defoliation (Marçais and Bréda, 2006). Other root pathogens have been shown to reduce rates of oak-seedling photosynthesis (Linaldeddu et al, 2009). Marçais et al (2011) found that inoculating seedlings with a combination of pathogens known to be associated with oak decline (C. fusipes, Armillaria mellea, and two Phytophthora spp.)…”
Section: Emergent Biotic Agents Involved In Oak Decline: Pathogensmentioning
confidence: 98%
“…Two species in particular, Diplodia corticola and Biscogniauxia mediterranea, were found to be the most widely distributed pathogens in declining cork oak forests; the first has been considered the most virulent cork oak pathogen (Linaldeddu et al 2009b;Luque et al 2000). Attacks of D. corticola, originally misidentified as Diplodia mutila, were reported on cork oak trees in Italy, Morocco, Portugal, Spain, and Tunisia (Alves et al 2004).…”
Section: Stem Branch and Twig Pathogensmentioning
confidence: 99%
“…On cork oak, D. quercina causes dark brown-toblack leaf spots, coalescing into larger necrotic areas at the end of the growing season; sometimes it also causes twig cankers. At the physiological level, infection of D. quercina on cork oak modifies the normal balance of some metabolic processes, including stomatal conductance and photosynthesis (Linaldeddu et al 2009b). D. quercina has been shown to produce in vitro several secondary bioactive metabolites, some of which are phytotoxic (Maddau et al 2011).…”
Section: Leaf Pathogensmentioning
confidence: 99%